THE EFFECTS OF LINGUISTIC INTELLIGENCE AND CLASSROOM CLIMATE’S PERCEPTION OF THE STUDENT’S ENGLISH CONVERSATION - Erlin Puspitasari (Universitas Indraprasta PGRI, 2020)
The explanatory study was aimed ad describing the effects of linguistic intelligence and classroom classroom climate perseption. From the population of all the principals of junior high school in Depok, West Java (600 people), a sample of 106 principals were randomly selected. The data were collected using a questionnaire and then analyzed statistically using SPSS analyses. The result showed that linguistic intelligence and classroom climate’s perception directly influence the student’s English conversation, and that there are indirect effects of linguistic intelligence on student’s English conversation through classroom climate’s perception.